2019
DOI: 10.1109/tcbb.2018.2835459
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Targetability Evaluation Approach for Vitiligo Proteome Extracted through Integration of Gene Ontologies and Protein Interaction Topologies

Abstract: Vitiligo is a well - known skin disorder with complex etiology. Vitiligo pathogenesis is multifaceted with many ramifications. A computational systemic path was designed to first propose candidate disease proteins by merging properties from protein interaction networks and gene ontology terms. All in all 109 proteins were identified and suggested to be involved in the onset of disease or its progression. Later, a composite approach was employed to prioritize vitiligo disease proteins by comparing and benchmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Compared with the healthy control, elevated CXCL12 was observed in the serum of vitiligo patients, with a higher secretion of CXCL12 in patients with progressive vitiligo. ROC curve pointed out a significant correlation between CXCL12 level and disease progression, especially in patients who appeared to be stable or even improved before recurrence [ 66 ]. Studies examined patient-derived melanocytes and skin samples, and found a significant increase in the expression of epidermal melanocyte-derived CXCL12, surrounded by CXCR4+ cells in early vitiligo [ 67 ].…”
Section: Interaction Between Chemokines and Oxidative Stress In The Development Of Vitiligomentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the healthy control, elevated CXCL12 was observed in the serum of vitiligo patients, with a higher secretion of CXCL12 in patients with progressive vitiligo. ROC curve pointed out a significant correlation between CXCL12 level and disease progression, especially in patients who appeared to be stable or even improved before recurrence [ 66 ]. Studies examined patient-derived melanocytes and skin samples, and found a significant increase in the expression of epidermal melanocyte-derived CXCL12, surrounded by CXCR4+ cells in early vitiligo [ 67 ].…”
Section: Interaction Between Chemokines and Oxidative Stress In The Development Of Vitiligomentioning
confidence: 99%
“…Studies examined patient-derived melanocytes and skin samples, and found a significant increase in the expression of epidermal melanocyte-derived CXCL12, surrounded by CXCR4+ cells in early vitiligo [ 67 ]. It is noted that CXCR4 and CXCL12 have been recognized as critical mediators for mobilizing the IFN-producing cells and Langerhans cells in the skin [ 66 , 68 ]. The in vivo animal studies further confirmed that CXCL12 enhanced the recruitment of APCs and T cells to the site's proximity to melanocytes, resulting in melanocyte destruction and pigmentation [ 67 ].…”
Section: Interaction Between Chemokines and Oxidative Stress In The Development Of Vitiligomentioning
confidence: 99%
“…Recent proteomic studies have also proposed a panel of proinflammatory factors like lysophosphatidylcholine, platelet‐activating factor, succinic acid, CXCL4, and CXCL7 to be potential vitiligo biomarkers 139 . There is also an elegant study integrating genomics and proteomics to define a vitiligo diseasome network, and further identified a series of potential biomarkers like CXCL12, fibronectin 1, chloride intracellular channel 1, catenin β1 140 . Albeit these results of proteomic studies might assist vitiligo diagnosis, their mechanical implication in vitiligo pathogenesis remain enigmatic.…”
Section: Innate Immune Activationmentioning
confidence: 99%
“…Vitiligo melanocytes exhibited a 55.3 times upregulation based on RNA analysis compared to normal melanocytes (36). CXCL12 is one of the top secretary proteins upregulated in vitiligo (37). Additionally, CXCL12 regulates the migration and differentiation of melanocyte precursors and may play a role in the repigmentation of vitiligo lesions.…”
Section: Chemokines Recruiting Both Innate and Adaptive Immune Cells ...mentioning
confidence: 99%